Nintedanib in Asian patients with progressive fibrosing interstitial lung diseases: Results from the INBUILD trial. Issue 5 (15th January 2023) - Inoue, Yoshikazu; Wells, Athol U.; Song, Jin Woo; Xu, Zuojun; Kitamura, Hideya; Suda, Takafumi; Okamoto, Masaki; Müller, Heiko; Coeck, Carl; Rohr, Klaus B.; Kolb, Martin; Brown, Kevin K.
Abstract: Background and Objective: In the INBUILD trial in patients with progressive fibrosing interstitial lung diseases (ILDs), nintedanib reduced the rate of decline in forced vital capacity (FVC) with an adverse event profile characterized mainly by gastrointestinal events. We analysed the effects of nintedanib in the subset of Asian subjects. Methods: Subjects with fibrosing ILDs other than idiopathic pulmonary fibrosis who had shown progression of ILD at any time within the prior 24 months despite management deemed appropriate in clinical practice were randomized to receive nintedanib or placebo. We analysed the rate of decline in FVC (ml/year) over 52 weeks in all Asian subjects and in Asian subjects with a usual interstitial pneumonia (UIP)‐like fibrotic pattern on high‐resolution computed tomography (HRCT). Results: One hundred sixty‐four subjects in the INBUILD trial were of Asian race. The rate of decline in FVC (ml/year) over 52 weeks in this subgroup was −116.8 in the nintedanib group and −207.9 in the placebo group (difference: 91.0 [95% CI: 8.1, 173.9]; nominal p  = 0.03). In Asian subjects with a UIP‐like fibrotic pattern on HRCT, the rate of decline in FVC (ml/year) over 52 weeks was −130.1 in the nintedanib group and −224.2 in the placebo group (difference: 94.1 [5.5, 182.7]; nominal p  = 0.04). Adverse events led to treatment discontinuation in 19.0% of the nintedanib group and 13.8% of the placebo group. Conclusion: In Asian patients with progressive fibrosing ILDs, nintedanib reduced the rate of decline in FVC with adverse events that were manageable for most patients. Abstract : The INBUILD trial was a randomized placebo‐controlled trial of nintedanib in patients with fibrosing ILDs that were progressing despite management in clinical practice. Data from the subgroup of Asian patients showed that nintedanib reduced the rate of decline in lung function with adverse events that were manageable for most patients.